Workplace Characteristics and Working Class Vote for the Old and New Right. (26th August 2015) - Arndt, Christoph; Rennwald, Line
Abstract: This article focuses on the role of plant size for working class vote. We argue that workplace size does matter for political behaviour. Workers in smaller plants are less unionized and therefore base their voting decisions more strongly on their cultural attitudes, which undermine the support for social democratic parties. Using data from the European Social Survey (2002–2010), we find that workers in small plants have more right‐wing attitudes and, consequently, vote for new and old right parties, contrarily to workers in larger plants. Our research points towards important structural explanations of working class support for the right and its cross‐national differences.